Performance assessment of multi-tube He II/He II heat exchanger using a single tube sample. (June 2022) - Rousset, B.; Millet, F.
Highlights: Pressurized superfluid helium thermally linked to a saturated superfluid cold source is commonly used to cool down superconducting devices. A new approach to design a compact and efficient He II/He II heat exchanger is proposed. Experiments fully validate the semi-predictive model. Abstract: Superconducting high-field magnets working in He II are usually immersed in a pressurized static He II bath. This pressurized He II bath is then connected through a heat exchanger to a saturated He II bath acting as a cold source. Due to the peculiar He II properties (very high heat conductivity), the conventional heat exchanger designs are not suitable here. Additionally, a compact design is often mandatory, as space inside cryostats is always an issue. In a recent paper [1], we presented different configurations of optimized multi tube heat exchangers depending on the available horizontal or vertical space. Such an optimized compact heat exchanger prototype has been built to fulfill the cooling needs and the integration constraints of the HL-LHC superconducting D2 recombination dipole [2]. The chosen design with hundred oxygen-free high-purity copper horizontal tubes penetrating inside the extremity of the D2 cold mass vessel is an efficient solution offering significant operating margins. From the thermal analysis, it appears that the profile and value of the temperature difference across the heat exchanger really depends on the ratio of the transverse conductance to the longitudinal conductance, the first being determined by the conductivity of the copper and the Kapitza conductance. Therefore, optimization and prediction of the thermal performance of such a heat exchanger is only possible when these thermal properties (i.e., the heat conductivity and Kapitza conductance of the copper tubes) or the sum of these three thermal resistances in series are well known. For that purpose, we built a dedicated test bench to perform these transverse resistance measurements on a pipe sample. The experimental results obtained on a single pipe were then used to infer the behavior of the complete heat exchanger. The comparison of the predictive code and the cryogenic measurements shows excellent agreement over a wide range of cryogenic operating conditions (temperatures, pressures, heat loads). This paper presents a guideline for designing compact and efficient He II/He II heat exchanger as well as a method to predict the performance of such heat exchanger accurately.